2014
DOI: 10.1038/srep07343
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Mucosal Trefoil Factors and Mucins in Pediatric Inflammatory Bowel Diseases

Abstract: In the intestinal mucosa trefoil factors (TFF) and mucins (Muc) - primarily produced by goblet cells - are thought to play a major role in providing barrier function during infection and inflammation. To investigate their role in pediatric Crohn's disease (CD) and ulcerative colitis (UC) we obtained mucosal biopsies of children with CD, UC and healthy controls and analyzed genetic expression. Levels of TFF2 mRNA were lower in inflamed mucosal samples (terminal ileum (TI) and duodenum) of children with CD, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 14 publications
(13 reference statements)
4
31
1
4
Order By: Relevance
“…TFF1 expression in the gastric mucosa is higher in the Helicobacter pylori (Hp)-positive patients than in the Hp-negative patients, but the discrepancy is not significant [73]. Researchers discovered that TFF1 expression was independent of both age and gender [10]. However, one study reported that in Hp-negative patients, TFF1 mRNA levels in women were notablely higher than in men, and they were significantly lower in positive than negative women [74].…”
Section: Distribution and Expressionmentioning
confidence: 94%
See 2 more Smart Citations
“…TFF1 expression in the gastric mucosa is higher in the Helicobacter pylori (Hp)-positive patients than in the Hp-negative patients, but the discrepancy is not significant [73]. Researchers discovered that TFF1 expression was independent of both age and gender [10]. However, one study reported that in Hp-negative patients, TFF1 mRNA levels in women were notablely higher than in men, and they were significantly lower in positive than negative women [74].…”
Section: Distribution and Expressionmentioning
confidence: 94%
“…In all TFF1-positive cancers, the protein is expressed in the cytoplasm of the tumor epithelial cells, as it is in normal gastric mucosal cells [10,25,72] (Fig. 2).…”
Section: Distribution and Expressionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, lower levels of trefoil factor 2, peptides abundantly secreted by goblet cells on the lumen surface, were reported in mucosal biopsy of children with IBD [45]. Recently, impaired differentiation of goblet cells from intestinal stem cells was found in inflammatory bowel diseases and this resulted in defective mucus layer [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are correlated with the severity of periodontal disease [26]. However, mucin 2 can even be inversely correlated with CXCL8 expression, at least in pediatric patients with Crohn's disease [27]. Also, different splice variants differ in their ability to modulate CXCL8 expression [28].…”
Section: Discussionmentioning
confidence: 99%